Interpretation of the Art of Bakhshi in the Works of Maksud Sheikhzade (Journal of Pedagogical Inventions and Practices, 2022)
The primordial history and culture of any nation is personified primarily by its oral creativity - folklore, folk epic and is an invaluable source in the preservation and development of national values and traditions. In this article, in the context of the analysis, the scientific views of the great Uzbek poet of the 20th century Maksud Sheikhzade on the essence of the national art of storytellers - bakhshi are considered. The reader develops a special broad thinking.